2011
DOI: 10.1088/0004-637x/735/1/19
|View full text |Cite
|
Sign up to set email alerts
|

Star-Forming Cloud Complexes in the Central Molecular Zone of NGC 253

Abstract: We report 350 and 230 GHz observations of molecular gas and dust in the starburst nucleus of NGC 253 at 20-40 pc (1 -2 ) resolution. The data contain CO(3-2), HCN(4-3), CO(2-1), 13 CO(2-1), C 18 O(2-1), and continuum at 0.87 mm and 1.3 mm toward the central kiloparsec. The CO(2-1) size of the galaxy's central molecular zone (CMZ) is measured to be about 300 pc × 100 pc at the half-maximum of intensity. Five clumps of dense and warm gas stand out in the CMZ at arcsecond resolution, and they are associated with … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
123
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 87 publications
(144 citation statements)
references
References 72 publications
21
123
0
Order By: Relevance
“…All these clumps are approximately 10 pc in size. Sakamoto et al (2011) identified five peaks in their 1.3 mm continuum map with 20 pc (1 .1) resolution. One of the peaks, peak 3, is resolved into four clumps in our continuum map (Clumps 2-5; see Figure 1 (a)), and it turns out that those have totally diverse spectral features (see Section 3.2).…”
Section: Observations and Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…All these clumps are approximately 10 pc in size. Sakamoto et al (2011) identified five peaks in their 1.3 mm continuum map with 20 pc (1 .1) resolution. One of the peaks, peak 3, is resolved into four clumps in our continuum map (Clumps 2-5; see Figure 1 (a)), and it turns out that those have totally diverse spectral features (see Section 3.2).…”
Section: Observations and Analysesmentioning
confidence: 99%
“…Rieke et al 1980); active star-formation in its central region with the star-formation rate of a few M yr −1 (e.g. Radovich et al 2001) is sustained by a large amount of interstellar medium (e.g., Sakamoto et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Turner & Ho (1985) observed over 60 compact radio sources, the brightest Reduced datacubes and extracted images for each line are only available at the CDS via anonymous ftp to cdsarc.u-strasbg.fr (130.79.128.5) or via http://cdsarc.u-strasbg.fr/viz-bin/qcat?J/A+A/550/A12 of which is named TH2. A high resolution (1 −2 ) study of the molecular gas in NGC 253 was performed by Sakamoto et al (2011). They found 5 warm, dense clumps of molecular gas, which are all coincident with radio sources.…”
Section: Introductionmentioning
confidence: 99%
“…We adopt D = 3.9 Mpc. The galaxy is highly inclined and the starburst CMZ also shows an inclined, disky structure (Sakamoto et al 2011 …”
Section: M83mentioning
confidence: 99%